Antecedents of work engagement in a multinational oil company - AL Olivier; S Rothmann (SA Journal of Industrial Psychology, 2007)
The objective of this study was to investigate the antecedents of work engagement. Stratified random samples (N=171) were taken of employees in a multinational oil company. The Work Engagement Scale and the Work Experiences Scale were administered. The results confirmed that psychological meaningfulness and psychological availability were significant predictors of work engagement. Psychological meaningfulness displayed the strongest positive relationship with engagement. The relationship of co-worker relations and work role fit with work engagement was mediated by the psychological condition of meaningfulness. Cognitive, emotional and physical resources had the strongest effect on psychological availability. Co-worker relations and co-worker norms predicted psychological safety. The relationship between resources and work engagement was mediated by the psychological condition of availability.